The World Bank Group and the Global Food Crisis: An Evaluation of the World Bank Group Response - WorldBank (World Bank, 2015)
The unanticipated spike in international food prices in 2007-08 hit many developing countries hard. International prices for food and other agricultural products increased by more than 100 percent between early 2007 and mid-2008. Prices for food cereals more than doubled; and those for rice doubled in the space of just a few months. The food price increases were particularly hard on the poor and near-poor in developing countries, many of whom spend a large share of their income on food and have limited means to cope with price shocks. An estimated 1.29 billion people in 2008 lived on less than $1.25 a day, equivalent to 22.4 percent of the developing world population. In addition, the Food and Agriculture Organization estimated that 923 million people were undernourished in 2007. Simulation models suggested that poverty rose by 100-200 million people and the undernourished increased by 63 million in 2008. The World Bank organized rapidly for short-term support in the crisis, launching a fast-track program of loans and grants, the Global Food Crisis Response Program (GFRP). The GFRP mainly targeted low-income countries, and provided detailed policy advice to governments and its own staff on how to respond to the crisis. The Bank also scaled up lending for agriculture and social protection to support the building of medium-term resilience to future food price shocks. The International Finance Corporation responded by sharply increasing access to liquidity for agribusinesses and agricultural traders in the short and medium term, as well as new programs to improve incentives for agricultural market participants. This evaluation assesses the effectiveness of the World Bank Group response in addressing the short-term impacts of the food price crisis and in enhancing the resilience of countries to future shocks.